Social Media and the Liabilities of Internet Service Providers in Nigeria: A Comparative Analysis of Jurisdictions - OLAGUNJU, Alex Tolu; Olugasa, Olubukola; Lalude, Olalekan Moyosore (Society & Sustainability, 2021)
Social media has been the vehicle for the dynamic progression of globalization. The purpose of social media encompasses many ends. Some of which allow for liabilities for third-party users, or in some circumstances, liabilities for Internet Service Providers. There are many complications in determining the liabilities of Internet Service Providers and third-party users. This paper examined the nature of Internet Service Providers (ISP), social media, and the activities of third-party users in Nigeria. It also interrogated the various instances where third party use of social media might affect ISP liability. This paper further explored the judicial and legal framework of some jurisdictions to see how they view the liabilities of internet service providers. The paper concluded that internet service providers should be held accountable for the content that is published on their platforms as it affects greatly the lives of concerned users offline.